Injury rates and mechanisms of starting and replacement players - Bitchell, L.; Robinson, G.; Stiles, V. H.; Mathema, P.; Moore, I. S. (International Journal of Performance Analysis in Sport, 2026)
To examine injury rates, injury mechanisms and injury inciting tackle characteristics of both starting and replacement players. A prospective, cohort study of four male professional Welsh Rugby Union (WRU) teams. Injury surveillance and Global Positioning System (GPS) data were collected from league matches between the 1st of July 2017 to the 31st of August 2020. Video analysis included league matches from the 1st of July 2017 to the 31st of March 2021. Player-specific GPS exposure was used to calculate injury incidence. Generalised linear mixed models were used to analyse the effect of replacement players on injuries. Tackle injury propensity (injuries/100 tackle events) and descriptive characteristics for the tackle event were reported. A total of 290 injuries were sustained by 105 players. Starting players had a higher injury incidence than replacement players (80.8 vs 57.2 injuries/1000 match hours; rate ratio: 1.41 (95% CI 1.00 - 1.98)). For every replacement used there was a 12% increase in the number of injuries (p = 0.037). However, there was no increase in the number of injuries accounting for the replacement time-in-game (p = 0.099). The injury propensity was highest for starting versus opposition replacement players (RR: 4.08, 95% CI: 2.28 - 7.29). Injury inciting tackles for starting players showed higher body positions, whereas replacement players maintained a lower body position. Match injuries were influenced by the number of replacement players, but this was mitigated when accounting for the replacement player time-in-game. Starting and replacement players have differing injury inciting tackle characteristics, suggesting that injury risk mitigation associated with the tackle should be incorporated at a player-specific level.